5 - Des approches méthodologiques à la recherche évaluative : les spécificités et les modalités de la recherche évaluative et ses liens avec la sociologie - Diop, Aladji Madior (Africa Development, 2021)
What is the dividing line between evaluative research and other types of research? On what modalities is it based? What is it that shapes its links with sociology? These are the questions to which the author of this paper attempts to provide answers. After presenting the different methodological approaches (trends) in sociology, he further demonstrated that evaluative research that has emerged as a distinct area of research has endorsed the methods and techniques of social research. As in most research disciplines, two major paradigms are explored, i.e. the empirical and normative paradigms that determine the approach adopted by the researcher who embarks on an evaluative research. This type of research which, in its infancy, developed diversified methods and techniques to measure the effectiveness and efficiency of social programmes, ceased to be at the service of management sciences from the end of the 1980s to focus on the issues of validity and social utility, thus adhering more closely to sociology.